Combining TMS and tACS for Closed-Loop Phase-Dependent Modulation of Corticospinal Excitability: A Feasibility Study - Raco, Valerio; Bauer, Robert; Tharsan, Srikandarajah; Gharabaghi, Alireza (Frontiers in Cellular Neuroscience, 2016)
Background: The corticospinal excitability indexed by motor evoked potentials (MEPs) following transcranial magnet stimulation (TMS) of the sensorimotor cortex is characterized by large variability. The instantaneous phase of cortical oscillations at the time of the stimulation has been suggested as a possible source of this variability. To explore this hypothesis, a specific phase needs to be targeted by TMS pulses with high temporal precision. Objective: The aim of this feasibility study was to introduce a methodology capable of exploring the effects of phase-dependent stimulation by the concurrent application of alternating current stimulation (tACS) and TMS. Method: We applied online calibration and closed-loop TMS to target four specific phases (0°, 90°, 180°, 270°) of simultaneous 20 Hz tACS over the primary motor cortex (M1) of seven healthy subjects. Result: The integrated stimulation system was capable of hitting the target phase with high precision (SD ± 2.05 ms, i.e. ± 14.45°) inducing phase-dependent MEP modulation with a phase lag (CI95% = - 40.37° to - 99.61°) which was stable across subjects (p=0.001). Conclusion: The combination of different neuromodulation techniques facilitates highly specific brain state-dependent stimulation, and may constitute a valuable tool for exploring the physiological and therapeutic effect of phase-dependent stimulation, e.g. in the context of neurorehabilitation.